2013
DOI: 10.1007/s12639-013-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-Toxoplasma gondii antibodies in cattle and pigs in Ibadan, Nigeria

Abstract: Toxoplasmosis is an important food borne parasitic zoonoses. However, data on Toxoplasma gondii infection in domestic animals mostly used for human consumption in Nigeria are scarce. We thus conducted a survey on the seroprevalence of T. gondii infection in a representative sample of cattle and pigs in farms and the abattoirs between June and December 2012. Sera from 210 cattle (both sexes) and 302 pigs (both sexes), were examined for T. gondii specific IgG antibodies by indirect Enzyme linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
1
27
2
Order By: Relevance
“…Our study indicates an increased seroprevalence of toxoplasmosis with age. This is in agreement with the reports of Zemene et al (2012) and Onyiche & Ademola (2015), who reported statistically significant association between age and toxoplasmosis. Nonetheless, the present study showed no significant association between age and toxoplasmosis.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Our study indicates an increased seroprevalence of toxoplasmosis with age. This is in agreement with the reports of Zemene et al (2012) and Onyiche & Ademola (2015), who reported statistically significant association between age and toxoplasmosis. Nonetheless, the present study showed no significant association between age and toxoplasmosis.…”
Section: Resultssupporting
confidence: 94%
“…In addition, the high prevalence in the former study could be attributed to the geographical location where the study was conducted. Ayinmode & Olaosebikan (2013) reported a similar prevalence of 25 % in a study conducted within the same geographical location as Onyiche & Ademola (2015). Animals reared outdoors are more prone to parasitic infections because they pick up parasites from contaminated environment.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Pigs and sheep are also commonly infected. Pigs are very susceptible to become experimentally infected and show high prevalence rates in some regions of the United States, as well in warm and tropical countries [16][17][18][19][20][21]. Prevalence rates of T. gondii in sheep are also widely distributed.…”
Section: Occurrence Of Toxoplasmosismentioning
confidence: 99%